High-intensity interval training versus moderate-intensity continuous training for polycystic ovary syndrome: a meta-analysis of randomized controlled trials - Zhao, Yi; Long, Yu; Zhu, Hongjiao; He, Run; Chen, Yunxia; Li, Jingrong (Frontiers in Endocrinology, 2025)
ObjectivePolycystic Ovary Syndrome (PCOS) is the most prevalent endocrine disorder affecting women of reproductive age. Lifestyle modifications, particularly exercise, are cornerstone management strategies, with High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT) being commonly recommended modalities. Despite their widespread use, high-quality evidence directly comparing HIIT and MICT in women with PCOS is limited. This meta-analysis aims to rigorously compare the effects of HIIT versus MICT in women with PCOS to provide precise and robust evidence for clinical recommendations.MethodsThis meta-analysis adhered to PRISMA guidelines, conducting a comprehensive search across PubMed, EMBASE, Web of Science, and Cochrane Library databases up to April 15, 2025. Randomized controlled trials (RCTs) directly comparing supervised HIIT and MICT interventions of at least 12 weeks in premenopausal women (18–50 years) diagnosed with PCOS were included. Outcome data covered anthropometric measures, cardiorespiratory fitness, glucose and insulin metabolism, lipid profile, and hormonal parameters. Methodological quality was assessed using the Cochrane Risk of Bias Tool (RoB 2), and overall evidence certainty was determined via GRADE methodology. Statistical analyses were performed using Review Manager (RevMan) 5.4.1, with continuous variables analyzed as Weighted Mean Differences (WMD) with 95% Confidence Intervals (CIs).ResultsA total of six RCTs were included in the meta-analysis. The main findings indicate no statistically significant superiority of either HIIT or MICT across anthropometric outcomes (weight, BMI, waist circumference, hip circumference, WHR), cardiorespiratory fitness (VO2max, SBP, DBP), glucose and insulin metabolism (fasting glucose, fasting insulin, HOMA-IR), lipid profile (total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides), or hormonal parameters (testosterone, SHBG, FAI). The certainty of evidence for these outcomes ranged from very low to low.ConclusionBased on the current low to very low certainty evidence from RCTs, there is no statistically significant superiority of HIIT over MICT for improving anthropometric, cardiorespiratory, metabolic, or hormonal outcomes in women with PCOS. These findings suggest that either HIIT or MICT can be recommended based on patient preference, but larger RCTs are needed due to low evidence certainty. This study received no funding.